Phonetic and Grammatical Characteristics of Mojtabā Minovi’s Pānzdah Goftār - Negar Khan Mohammadi; Naser Rahimi (مطالعات زبانی و بلاغی)
Mojtabā Minovi (1903-1977), a renowned scholar from the recent past, paid much attention to Persian prose and tried to use nuances and techniques in his writings that helped improve the prose. Therefore, analyzing his prose is deemed beneficial. Among his works, Pānzdah Goftār (Fifteen Speeches), first published in 1954, was selected to examine the phonetic and grammatical characteristics of this book. Based on a layered stylistics method, our search shows that Minovi paid great attention to the phonetic and grammatical characteristics of language and historical phonology of Persian. This led him to use nuances in Fifteen Speeches that are less common in contemporary prose. For example, he used the archaic forms of some words such as asp (horse), afgandan (to throw), and peygar (combat), or included Arabic diacritics to indicate the precise pronunciation of non-Iranian words and names, including European and non-European ones. He also used aslan and asla in two different meaning (originally versus never), and some other cases. At the grammatical level, the prose of Fifteen Speeches also has its own characteristics. For example, he used feminine Arabic adjectives for broken/internal plural (jam'-e mokassar) or singular Arabic nouns, compound prepositions in their complete form, such as az baraye (for), dar tahte (under), and dar moghe-ye (while), singular verb for a non-human plural subject, descriptive (participial) form frequently, and other such characteristics.